Efektivitas Program Keluarga Berencana Pria di Kecamatan Curup Utara Kabupaten Rejang Lebong - Desi Andriani; Djonet Santoso; Pardamean Daulay (LPPM Institut Pesantren KH. Abdul Chalim, 2022)
The aim of this study is to see the effectiveness of Keluarga Berencana for man program in Curup Utara sub-district Rejang Lebong regency seen from source approach, process approach and target approach by using qualitative method as narratively. In determining informants for data of this study, purposive sampling is taken then analyzed in the stage of data reduction, data display and drawing conclusion. Based on the result of this study, this program has been good enough seen from source approach include capable medic workers, adequate medic and contraception supply for society while it' s still not good enough for process approach because lack of socialization of Keluarga Berencana for man to society even BKKBN delegete their duty to midwife and cadre to sociallize it to society. For target approach, it is still not good enough because unreached target from implemented program. It is recommended for BKKBN Rejang Lebong to coordinate with Village head to socialize this program directly by visiting people houses, not only through POSYANDU or SAFARI KB, but also improving the coordination and teamwork among of PUSKESMAS, Village midwife, and cadre to socialize Keluarga Berencana for man